Christianity in the Roman Empire : key figures, beliefs, and practices of the early Church, AD 100-300 - Winn, Robert E. (Peabody, Massachusetts : Hendrickson Publishers Marketing, LLC, 2018)
Christianity in the Roman Empire is a topical and biographical introduction to Christianity before Constantine. While its focusis the historical development of the proto-orthodox community, Robert Winn aims to bridge the gap between contemporary Christians and those who lived in the Roman Empire. To do this, his chapters discuss particular topics such as prayer, biblical interpretation, worship, and persecution, as well as prominent and controversial individuals such as Ignatius of Antioch, Justin Martyr, Melito of Sardis, and Tertullian. Part One addresses the world of the apostolic fathers, Part Two addresses hostility to Christianity and the response of Christians to this antagonism, and Part Three addresses doctrinal and communal issues of the third century.The book will pique readers' interest and provide them with a deeper appreciation for the religious identity of early Christians in the Roman Empire: what they believed and how they lived.Part One: Christianity in the Year 1001. Christians, Jews, and Romans in the First Century2. New Way of Life: Didache and the Epistle of Barnabas3. Clement of Rome and the Church of Corinth4. Ignatius of Antioch and True Christianity5. Worship and Church Order in the Year 100Part Two: Christianity in a Hostile World (100-250)6. Celsus, a Critic of Christianity7. Justin Martyr, a Defender of Christianity8. The Persecution of Christians9. The Martyrdom of Perpetua and Felicity10. Cyprian of Carthage and the Unity of the ChurchPart Three: Faith and Practice in the Third Century11. Reading the Bible with Early Christians12. Irenaeus of Lyons and True Christianity13. Tertullian of Carthage and True Christianity14. Prayer and the Spiritual Life of Early Christians15. Eusebius of Caesarea: After Two Hundred Years.
Part I: Christianity in the year 100. Christian, Jews and Romans in the first century ; A new way of life: Didache and the Epistle of Barnabas ; Clement of Rome and the church of Corinth ; Ignatius of Antioch and true Christianity ; Worship and the church order in the year 100 -- Part II: Christianity in a hostile world (AD 100-250). Celsus, a critic of Christianity ; Justin Martyr, a defender of Christianity ; The persecution of Christians ; The martyrdom of Perpetua and Felicity ; Cyprian of Carthage and the unity of the church -- Part III: Faith and practice in the third century. Reading the Bible with early Christians ; Irenaeus of Lyons and true Christianity ; Tertullian of Carthage and true Christianity ; Prayer and the spiritual life of early Christians ; Eusebius of Caesarea: after two hundred years
Includes bibliographical references.
Description based on online resource; title from PDF title page (EBSCO, viewed June 5, 2019).
Added to collection customer.56279.3
Keywords: Church history -- Primitive and early church, ca. 30-600.; Church history -- Primitive and early church; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books